Machine tool operations visutext. - Krar, Steve F (Glencoe Division of Macmillan/McGraw Hill, 1990)
Measurement series -- Bench series -- Drill press series -- Lathe series -- Shaper series -- Horizontal milling machine series -- Vertical mill series -- Surface grinder series